Cell Therapy for Retinal Degenerative Diseases: Progress and Prospects - Kevin Y. Wu; Jaskarn K. Dhaliwal; Akash Sasitharan; Ananda Kalevar (MDPI AG, 2024)
Background/Objectives: Age-related macular degeneration (AMD) and retinitis pigmentosa (RP) are leading causes of vision loss, with AMD affecting older populations and RP being a rarer, genetically inherited condition. Both diseases result in progressive retinal degeneration, for which current treatments remain inadequate in advanced stages. This review aims to provide an overview of the retina's anatomy and physiology, elucidate the pathophysiology of AMD and RP, and evaluate emerging cell-based therapies for these conditions. Methods: A comprehensive review of the literature was conducted, focusing on cell therapy approaches, including embryonic stem cells (ESCs), induced pluripotent stem cells (iPSCs), mesenchymal stem cells (MSCs), and retinal progenitor cells. Preclinical and clinical studies were analyzed to assess therapeutic potential, with attention to mechanisms such as cell replacement, neuroprotection, and paracrine effects. Relevant challenges, including ethical concerns and clinical translation, were also explored. Results: Cell-based therapies demonstrate potential for restoring retinal function and slowing disease progression through mechanisms like neuroprotection and cell replacement. Preclinical trials show promising outcomes, but clinical studies face significant hurdles, including challenges in cell delivery and long-term efficacy. Combination therapies integrating gene editing and biomaterials offer potential future advancements. Conclusions: While cell-based therapies for AMD and RP have made significant progress, substantial barriers to clinical application remain. Further research is essential to overcome these obstacles, improve delivery methods, and ensure the safe and effective translation of these therapies into clinical practice.